Pengembangan Kampung Kopi Tebes Lues dengan Pendekatan Sustainable Community-Based Tourism - Suraiya Kamaruzzaman; Rusman; Cut Dewi; Friesca Erwan; Fitriana (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Jakarta, 2024)
Tebes Lues Village, located in Bies District, Central Aceh Regency, is the only Coffee Village (Kampung Kopi) in the Aceh region. The village development concept focuses on empowering the community to manage coffee farming into value-added products through a community-based tourism (CBT) approach. However, several challenges hinder the development of Kampung Kopi Tebes Lues, including limited local knowledge regarding CBT implementation, the absence of a tourism management group, and the lack of legal certification for local small and medium enterprises (SMEs) to sell their products in society at large. To address these issues, a series of activities were organized, engaging the active participation of community members, academics, facilitators, and practitioners. The implementation process was divided into three phases: preparation, execution, and monitoring and evaluation. Several outcomes were achieved, including product licensing documents, intellectual property (IP) registration for product branding, and the establishment of a tourism management group through collaborative discussions between the service team and the local community. Future steps involve collaboration with local government and continued community assistance to enhance tourism-based economic activities in Tebes Lues Village. Keywords: community-based tourism, community empowerment, Kampung Kopi Tebes Lues, village tourism. Desa Tebes Lues di Kecamatan Bies, Kabupaten Aceh Tengah, merupakan satu-satunya Kampung Kopi di Aceh. Konsep pengembangan desa ini berfokus pada pemberdayaan masyarakat dalam mengelola pertanian kopi menjadi produk bernilai tambah melalui pendekatan community-based tourism (CBT). Namun, terdapat beberapa kendala, seperti rendahnya pengetahuan masyarakat tentang implementasi CBT, belum terbentuknya kelompok penggerak pariwisata yang mengkoordinasi kegiatan berbasis wisata, serta belum adanya legalitas produk UMKM untuk pemasaran komersial. Untuk mengatasi masalah tersebut, dilakukan serangkaian kegiatan yang melibatkan partisipasi aktif masyarakat, akademisi, fasilitator, dan praktisi. Metode pelaksanaan dibagi dalam tiga tahap: persiapan, pelaksanaan, serta pemantauan dan evaluasi. Kegiatan ini menghasilkan beberapa luaran, seperti dokumen pengusulan izin edar produk, pendaftaran merek HKI, dan pembentukan pengurus kelompok penggerak pariwisata. Tindak lanjut yang diperlukan adalah kolaborasi dengan pemerintah daerah dan pendampingan berkelanjutan untuk mengembangkan ekonomi berbasis pariwisata di Desa Tebes Lues. Kata kunci: community-based tourism, Kampung Kopi Tebes Lues, pariwisata desa, pemberdayaanmasyarakat.